2021
DOI: 10.1002/ehf2.13261
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter diagnostic sensor measurements during clinically stable periods and worsening heart failure in ambulatory patients

Abstract: Aims This study aims to characterize the range of implantable device-based sensor values including heart sounds, markers of ventilation, thoracic impedance, activity, and heart rate for patients with heart failure (HF) when patients were deemed to be in clinically stable periods against the time course of acute decompensation and recovery from HF events. Methods and results The MultiSENSE trial followed 900 patients implanted with a COGNIS CRT-D for up to 1 year. Chronic, ambulatory diagnostic sensor data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…Confirming previous findings, 12 we showed that, at the time of device detection of the HF event, the sensed parameters that contribute to the calculation of the HeartLogic index presented changes from their baseline reference values. In the present analysis, the accelerometer‐based third heart sound, a surrogate of filling pressure, 16 significantly increased, as did the respiratory rate, which is known to facilitate the identification of patients at risk of worsening HF 17 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Confirming previous findings, 12 we showed that, at the time of device detection of the HF event, the sensed parameters that contribute to the calculation of the HeartLogic index presented changes from their baseline reference values. In the present analysis, the accelerometer‐based third heart sound, a surrogate of filling pressure, 16 significantly increased, as did the respiratory rate, which is known to facilitate the identification of patients at risk of worsening HF 17 .…”
Section: Discussionsupporting
confidence: 90%
“…Normality of distribution was tested by means of the Kolmogorov–Smirnov test. The time course of HeartLogic index and sensor changes surrounding the decongestive treatment adjustment were evaluated at four time‐points, as in a previous study 12 . A 30‐day baseline was compared both with a 7‐day preaction state measured up until the day before the diuretic augmentation, and with the state on the first day of the augmented therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first heart sound (S1) is caused by the closure of the atrioventricular valves, its amplitude is affected by the pressure gradient across the atrioventricular valve [7]. The previous studies showed that its amplitude was correlated with myocardial contractility…”
Section: S1mentioning
confidence: 99%
“…Apart from the MultiSENSE study (and several post hoc analyses from this study), data on the performance of the HeartLogic TM algorithm are scarce. A few studies showed that patients in alert status have an increased risk of congestion as compared to patients not in alert status (10)(11)(12)(13). HeartLogic TM alerts are frequently actionable and clinical action seemed to lower the decompensated heart failure event rate compared to a wait and see strategy (10,14).…”
Section: Introductionmentioning
confidence: 99%